Juridical Overview of Unlawful Control of Land Owned by Homeless People - Bagus Raharjo S. Hidayat; Ahmad Riyadh U. B. (Indonesian Journal of Law and Economics Review, 2020)
The homeless phenomenon is very disturbing for the community. Moreover, homeless people have carried out land tenure unilaterally and against the law of someone's land. Furthermore, the purpose of this study is to measure the legal wisdom that can be done by land owners controlled by the Homeless. This research is a normative legal research using a statute approach. By using deductive analysis techniques using legal material processing methods in general. So that it can be analyzed legal problems based on facts in the field or in the community. The results of the study can be denied that the law enforcement of land tenure against the law by homeless people. Can be done in litigation or non-litigation. Litigation measures can be made in criminal and civil cases. The criminal mechanism is carried out by reporting to the police regarding the criminal law stipulated in Article 167 and Article 385 of the Criminal Code. A civil mechanism, the ruler of land and / or buildings thereon can be sued on the basis of an unlawful act along with an application for vacant land Non-litigation legal remedies can be made through complaints to the Satpol PP in the jurisdiction (locus) of the owner of the land rights. Satpol PP is an extension of the Ministry of Social Affairs and Provincial, Regency or City Government.